Synthesis and Structure−Activity Relationships of Benzothienothiazepinone Inhibitors of Protein Kinase D - Bravo-Altamirano, Karla (American Chemical Society, 2010)
[Image: see text] Protein kinase D (PKD) is a member of a novel family of serine/threonine kinases that regulate fundamental cellular processes. PKD is implicated in the pathogenesis of several diseases, including cancer. Progress in understanding the biological functions and therapeutic potential of PKD has been hampered by the lack of specific inhibitors. The benzoxoloazepinolone CID755673 was recently identified as the first potent and selective PKD inhibitor. The study of structure−activity relationships (SAR) of this lead compound led to further improvements in PKD1 potency. We describe herein the synthesis and biological evaluation of novel benzothienothiazepinone analogues. We achieved a 10-fold increase in the in vitro PKD1 inhibitory potency for the second generation lead kb-NB142-70 and accomplished a transition to an almost equally potent novel pyrimidine scaffold, while maintaining excellent target selectivity. These promising results will guide the design of pharmacological tools to dissect PKD function and pave the way for the development of potential anticancer agents.